Ø¯ÙˆØ± Ø§Ù„Ø¨ÙŠØ¦Ø© Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙÙŠ ØªÙ†Ù…ÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… Ù„Ø·Ù„Ø§Ø¨ Ø§Ù„Ù…Ø¹Ù‡Ø¯ Ø¯Ø§Ø± Ø§Ù„Ø³Ù„Ø§Ù… Ø³ÙŠØºÙˆÙ† Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬ - Wahdatussurur Assaidah; Muâ€™at; Abdul Ghofur (Program Studi Pendidikan Bahasa Arab, 2021)
The environment is one's first facility to get any language, either mother tongue or second language. Arabic as a second language (foreign) can be obtained through the Arabic environment otherwise known as the